High-sensitivity Troponin (hs-Tn) for Cardiovascular Risk Prognostication: A Systematic Review and Meta-analysis - Sagris, Marios; Antonopoulos, Alexios S.; Angelopoulos, Andreas; Papanikolaou, Paraskevi; Simantiris, Spyridon; Vamvakaris, Constantinos; Koumpoura, Alkmini; Farmaki, Maria; Antoniades, Charalambos; Tsioufis, Constantinos; Tousoulis, Dimitris (Current Medicinal Chemistry, 2024)
Background: Chronic low-grade inflammation is involved in coronary atherosclerosis progression whereas recent research efforts suggest that preventative methods should be tailored to the “residual inflammatory risk”. As such, modalities for the early identification of the risk have to be investigated. Methods: We performed a systematic review and meta-analysis according to the PRISMA guidelines. Any study that presented the prognostic value of high sensitivity troponin (hs-cTn) of vascular inflammation in stable patients without known cardiac heart disease was considered to be potentially eligible. The Medline (PubMed) database was searched up to April 22, 2021. The main endpoint was the difference in c-index (Δ[c-index]) with the use of hs-cTn for major adverse cardiovascular events (MACEs), cardiovascular and all-cause mortality. We calculated I2; to test heterogeneity. Results: In total, 44 studies and 112,288 stable patients without known coronary heart disease were included in this meta-analysis. The mean follow-up duration of the whole cohort was 6.8 ± 1.1 years. 77,004 (68.5%) of the patients presented at low cardiovascular risk while 35,284 (31.5%) in high. The overall pooled estimate of Δ[c-index] for MACE was 1.4% (95%CI: 0.7-2.1, I2;=0%) and for cardiovascular death 1.3% (95%CI: 0.3-2.3, I2;=0%). Finally, the overall pooled estimate of Δ[c-index] for all-cause mortality was 3% (95%CI: 1.9-3.9, I2;=86%), while high heterogeneity was observed between the studies. Conclusion: The predictive usefulness of changes in hs-cTn measures in stable individuals with either high or low cardiovascular risk, demonstrates that assessing vascular inflammation in addition to clinical risk factors enhances risk prediction for cardiovascular events and allcause mortality. Further prospective studies are necessary to confirm these findings and assist clinical decision-making regarding the most optimal prevention strategy.
Keywords: hs-Tn